THE USE OF DIGITAL IMAGE PROCESSING IN ANALYSIS OF BORON, CADMIUM IN THORIUM OXIDE WITHOUT CARRIER DISTILATION WITH EMISSION SPECTROGRAPH METHOD - Sahat Simbolon; Aryadi Aryadi; Muhtadan Muhtadan (Website, 2012)
THE USE OF DIGITAL IMAGE PROCESSING IN ANALYSIS OF BORON, CADMIUM IN THORIUM OXIDEWITHOUT CARRIER DISTILLATION EMISSION SPECTROGRAPH METHOD. The use of digital imageprocessing in direct determination elements of highly absorption cross-section of thermal neutron such as B andCd in nuclear fuel ThO2 without carrier distillation was described. Working and counter electrode should bemodified because volume of the sample was larger than the traditional one. Firstly, analysis of B and Cd in ThO2was recorded by X-ray film for thorax and then was proceeded by mini digital camera. All files in mini digitalcamera were transferred to computer and read by digital image processing of Matlab software. It was found thatall line spectra became Gaussian shape. Since couple of camera position and lightening system had not beendone successfully yet, therefore, quantitative analysis could not been done yet, meanwhile qualitative analysishad already been done by analysis spectra after image processing. It is easier to analysis B and Cd qualitativelyuse of image processing than densitometer instrument.Keywords : Thorium Oxide, Carrier Distillation, Image Processing, Digital Camera